Investigação de uma abordagem pedagógica para o ensino de língua inglesa por meio de jogos digitais - Centenaro, Franciele Knebel (2016)
The use of technology in the classroom has constantly challenged students and teachers (KENSKI, 2005), it happens because in this context there is a new generation of students who are capable to use technologies (BARBOSA, 2010), that is, they use and manage digital technologies like computers, smartphones and videogames. In this sense, teaching materials do not always call the attention of these young students, and learning in a traditional way can demotivate them, since emerging technologies attract much more their attention (REIS, 2015). Therefore, considering the paradigm schools are facing nowadays and from the need as English language teacher understand how the use of digital games can be explored in languages learning classes, we investigate digital learning games based on the learning principles proposed by Gee (2005) and designed a pedagogical proposal focused in the concept of language teaching approach developed by Almeida Filho (2002), the Digital Teaching Material Cycle (REIS; GOMES, 2014), the genre and multiliteracies pedagogy principles (ROSE; MARTIN, 2012; COPE; KALANTZIS, 2015) and the Game Activity Design Framework suggested by Reinhardt (2011 apud SYKES, 2013). In this way, an action research was applied in the research line of Educational Technology Management Network, at the professional master's program in Educational Technology Network, with foreign language students in regular classroom at English Language course. The corpora was collected by teaching participant observation and by the implemented instruments, such as diagnostic and assessment questionnaires, filming and activities developed at Virtual Learning Environment. The results show as a final product, a pedagogical approach that uses digital learning games in language teaching to enhance the learning of vocabularies, the improvement of the English language skills and the practice of multiliteracies, which is named Language Teaching through Digital Learning Games cycle, that includes seven stages (Context analysis; Game analysis; Planning activities; Game practice; Practice in group; Activities practice; and Accountability). We believe that from this approach, language teachers can promote their practice by the use of digital learning games in schools, developing a contemporary education that matches to the today student's interests.